Sequence Composition of Bacterial Chromosome Clones in a Transgressive Root-Knot Nematode Resistance Chromosome Region in Tetraploid Cotton - Wang, Congli; Ulloa, Mauricio; Nichols, Robert L.; Roberts, Philip A. (Frontiers in Plant Science, 2020)
Plants evolve innate immunity including resistance genes to defend against pest and pathogen attack. Our previous studies in cotton (Gossypium spp.) revealed that one telomeric segment on chromosome (Chr) 11 in G. hirsutum cv. Acala NemX (rkn1 locus) contributed to transgressive resistance to the plant parasitic nematode Meloidogyne incognita, but the highly homologous segment on homoeologous Chr 21 had no resistance contribution. To better understand the resistance mechanism, a bacterial chromosome (BAC) library of Acala N901 (Acala NemX resistance source) was used to select, sequence, and analyze BAC clones associated with SSR markers in the complex rkn1 resistance region. Sequence alignment with the susceptible G. hirsutum cv. TM-1 genome indicated that 23 BACs mapped to TM-1-Chr11 and 18 BACs mapped to TM-1-Chr 21. Genetic and physical mapping confirmed less BAC sequence (53–84%) mapped with the TM-1 genome in the rkn1 region on Chr 11 than to the homologous region (>89%) on Chr 21. A 3.1-cM genetic distance between the rkn1 flanking markers CIR316 and CIR069 was mapped in a Pima S-7 × Acala NemX RIL population with a physical distance ∼1 Mbp in TM-1. NCBI Blast and Gene annotation indicated that both Chr 11 and Chr 21 harbor resistance gene-rich cluster regions, but more multiple homologous copies of Resistance (R) proteins and of adjacent transposable elements (TE) are present within Chr 11 than within Chr 21. (CC)-NB-LRR type R proteins were found in the rkn1 region close to CIR316, and (TIR)-NB-LRR type R proteins were identified in another resistance rich region 10 cM from CIR 316 (∼3.1 Mbp in the TM-1 genome). The identified unique insertion/deletion in NB-ARC domain, different copies of LRR domain, multiple copies or duplication of R proteins, adjacent protein kinases, or TE in the rkn1 region on Chr 11 might be major factors contributing to complex recombination and transgressive resistance.